Features Of The Subject Composition As A Criterion For The Systematization Of Treaties In The International Private Law - Musabirova, Dinara Anvarovna (2017)
This article is an attempt to study the system-forming criteria of civil law treaties complicated by a foreign element.The common goal of establishing the treaties within the agreed system is the creation of a structure, the logical harmonization of agreements, schemes and a mechanism for the regulation of economically important relations of a transboundary nature. A competent system approach predetermines the primary achievement of the law-making goal - the organization of effective impact of modern legislation on the emerging legal relationships. It is the criterion of such systematization, correctly chosen and used, is the guarantee of the formation of an effective legal canvas.It is concluded that the foreign element does not affect the substance of the transactions under consideration. However, a special status of the parties to the agreements causes the emergence of specific features of their legal regulation that allow using the subject composition of treaty relations of an international nature as a system-forming criterion of great importance, including from the point of view of law enforcement practice. Further doctrinal and practical study of such features is seen as important and theoretically interesting